An analysis of the machinability of ASTM grades 2 and 3 austempered ductile iron - Davi Melo Montenegro (2011)
Austempered Ductile Iron (ADI) is a ferrous material that was first fabricated in the second half of last century, therefore a relatively new material compared to steel, which has been used for different applications by mankind for some millennia now. ADI';s mechanical properties, such as its strength-to-weight ratio, which has proven to outperform that of forged steel by up to 10%, are very suitable for structural applications, such as connecting rods, crankshafts, and heavy farm machinery among others. The main goal of this work is to perform an analysis of the machinability of two ASTM grades of ADI, namely 2 and 3. The samples used in this work were cast and austempered according to ASTM standards for the production of grade 2 (G2) and grade 3 (G3) ADI. Characterization was accomplished through tensile and hardness tests, metallography and X-ray diffraction. Machinability was evaluated by analyzing tool life, cutting forces, surface finish and chip characteristics in turning operations. A quick-stop test was also performed. Tool life when machining G2 was 33% lower than G3, although the latter is a harder material. Abrasion and adhesion were the wear mechanisms observed through SEM images, whereas in other cast irons mainly abrasion is observed. Cutting forces measurements showed that the value of Kc1,1 decreased 19%, from 1448 to 1175N/mm2, for G2 as the depth of cut increased from 2 to 5mm at a cutting speed of 80m/min and 18%, from 1501 to 1236N/mm2, for G3. Surface roughness measurements proved that a smoother surface is obtained for both alloys at f = 0.10mm/rev when using an insert with nose radius 1.6mm instead of smaller radii. Both alloys presented similar surface quality. All chips observed were segmented.